Komiks salamin ng pusong Pinoy - Aguilar, Mila D.; Selvido, Ma. Ernie (The Institute, 1989)
Shows why comics remain a popular reading form among Filipinos, as explained by comics writers, a sociologist, a psychologist and the ordinary people on the street.